Modeling flux in tangential flow filtration using a reverse asymmetric membrane for Chinese hamster ovary cell clarification. (2nd January 2021) - Zhang, Da; Patel, Parag; Strauss, Daniel; Qian, Xianghong; Wickramasinghe, S. Ranil
Abstract: Tangential flow filtration is advantageous for bioreactor clarification as the permeate stream could be introduced directly to the subsequent product capture step. However, membrane fouling coupled with high product rejection has limited its use. Here, the performance of a reverse asymmetric hollow fiber membrane where the more open pore structure faces the feed stream and the barrier layer faces the permeate stream has been investigated. The open surface contains pores up to 40 μm in diameter while the tighter barrier layer has an average pore size of 0.4 μm. Filtration of Chinese hamster ovary cell feed streams has been investigated under conditions that could be expected in fed batch operations. The performance of the reverse asymmetric membrane is compared to that of symmetric hollow fiber membranes with nominal pore sizes of 0.2 and 0.65 μm. Laser scanning confocal microscopy was used to observe the locations of particle entrapment. The throughput of the reverse asymmetric membrane is significantly greater than the symmetric membranes. The membrane stabilizes an internal high permeability cake that acts like a depth filter. This stabilized cake can remove particulate matter that would foul the barrier layer if it faced the feed stream. An empirical model has been developed to describe the variation of flux and transmembrane pressure drop during filtration using reverse asymmetric membranes. Our results suggest that using a reverse asymmetric membrane could avoid severe flux decline associated with fouling of the barrier layer during bioreactor clarification.